2013
DOI: 10.1177/0093854813500958
|View full text |Cite
|
Sign up to set email alerts
|

Does One Size Fit All?

Abstract: The application of common risk assessment measures, such as the Level of Service Inventories (LSI), to Aboriginal offenders has been a criticized practice. The belief that Aboriginal offenders have distinct needs has informed the argument that existing risk-need assessments cannot adequately capture their risk. To explore this, the present meta-analysis reviewed 16 samples to test the extent to which LSI scores predict recidivism for Aboriginal compared with non-Aboriginal offenders. In addition, one large sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 35 publications
8
65
0
Order By: Relevance
“…What these findings demonstrate is that there are likely variables and contextual circumstances unique to Aboriginal group membership, and not necessarily tied to risk or treatment performance per se, that partly account for the higher rates of general violent recidivism observed in this group (see Wilson & Gutierrez, 2014, for a detailed analysis of possible considerations). Thus, risk and change information on its own does not explain all individual differences in recidivism rates at least for general violence.…”
Section: Discussionmentioning
confidence: 85%
“…What these findings demonstrate is that there are likely variables and contextual circumstances unique to Aboriginal group membership, and not necessarily tied to risk or treatment performance per se, that partly account for the higher rates of general violent recidivism observed in this group (see Wilson & Gutierrez, 2014, for a detailed analysis of possible considerations). Thus, risk and change information on its own does not explain all individual differences in recidivism rates at least for general violence.…”
Section: Discussionmentioning
confidence: 85%
“…Third, the LS scales have been found to have general applicability across many forensic populations. This includes adults and youth in custody or on community supervision, male and female populations, and various ancestral/ethnic backgrounds and cultures on diverse measures of recidivism, ranging from technical violations to criminal charges and convictions (e.g., Olver et al, 2009;Smith et al, 2009;wilson & Gutierrez, 2014). Fourth, the LS scales have multiple applications in corrections.…”
Section: The Level Of Service (Ls) Family Of Risk-assessment Toolsmentioning
confidence: 99%
“…Taken together, evidence on the predictive validity of the Central Eight for ethnic minorities or culturally diverse (sub)samples is ambiguous. While some authors propose the cross-cultural transferability (Bhutta & Wormith, 2016;Olver et al, 2014;Takahashi, Mori, & Kroner, 2013;Zhang, & Liu, 2015), in some studies trends of reduced predictive power have been reported (Gutierrez, Wilson, Rugge, & Bonta, 2013;Onifade, Davidson, & Campbell, 2009;Singh, Grann, Fazel, 2011;Wilson & Gutierrez, 2014;Wormith, Hogg, & Guzzo, 2015) and yet in others a total lack of predictive validity was found (e.g., Dahle & Schmidt, 2014;Schlager & Simourd, 2007;Shepherd, et al, 2015). Furthermore, offenders with an MB from Turkey or Arab countries have rarely been studied, although they comprise a large percentage of European prison populations.…”
Section: Disparities In Predictive Validity Of the Central Eightmentioning
confidence: 99%